The political economy of NPOs promoting "active ageing" programs for the elderly in Taiwan - Tzeng, C (2016)
From the 1990s, welfare state and civil society in Taiwan were confronted with challenges and opportunities brought by population ageing. The author chooses NPOs with "Active Ageing" programs for the elderly, a group thriving as a consequence of Taiwan's unique transitional democratization and privatization under Neoliberalism, as a case to systematically investigate the governance structure. Four core NPOs of various scales and capacities are sampled while their stakeholders are also interviewed. Findings reveal that after the pension reform made possible by social movement and electoral politics, these institutionalized social forces secure their position in the welfare delivery system. However, problems remain unresolved because of structural inertia while NPOs operate under the changing field frame and conflicting institutional logics between the welfare state and civil society. Though partially impeded, NPOs develop an East-Asian way of solution with various counterplots. Contrasting rationales of networking explain NPOs' diverse achievements while quasi-subordination and structural loop consolidate respective constituency. Four patterns of perceived relational social capital relate to NPOs' networking practices and institutional settings. The connection among institutions, networking configurations, and relations further crystalizes the tripartite governance structure composed of the institutional, technical, and social environment. Legitimation of means functions mainly within the institutional environment while legitimation of ends through technical and social environment also justifies NPOs' social appropriateness. Various types of legitimacy are conferred to NPOs at different development stages while both formal and informal norms guide NPOs' behavior in the two-dimensional governing kinetics. Through this case study, the author also demonstrates how a meso-level approach of organizational study, integrating Sociological Institutionalism and Organizational Social Capital Theory, possibly sheds lights on the different areas of Sociology, especially those of social movement, NPOs, and ageing society.